2019
DOI: 10.3390/ma12142214
|View full text |Cite
|
Sign up to set email alerts
|

Influence of BOF and GGBFS Based Alkali Activated Materials on the Properties of Porous Concrete

Abstract: In this study, environmentally friendly ground granulated blast furnace slag (GGBFS) based alkali activated materials and basic oxygen furnace slags (BOFs) were used as bonding materials and aggregates, respectively, to produce novel, environmentally friendly GGBFS based porous concrete. Porous concrete with a particle size of 4.75–9.5 mm and 9.5–19.00 mm was used as an aggregate. The “liquid-to-solid ratios” (L/S) variable was set at set at 0.5 and 0.6, and the “percentage of pore filling paste ratio” variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Advances in Civil Engineering this study. e SG for BOFS is similar to the SG observed by Kuo et al [47], who reported a value of 3.31.…”
Section: Atterberg Limits and Specific Gravity Of Gmt And Bofssupporting
confidence: 88%
“…Advances in Civil Engineering this study. e SG for BOFS is similar to the SG observed by Kuo et al [47], who reported a value of 3.31.…”
Section: Atterberg Limits and Specific Gravity Of Gmt And Bofssupporting
confidence: 88%
“…These exothermic and complex geopolymer reactions contain large amounts of free silicon (f-SiO 2 ). This f-SiO 2 can react with f-CaO and f-MgO in the BOFS aggregate, and hence, the formation of stable compounds such as wollastonite (CaSiO 3 ) and enstatite (MgSiO 3 ) takes place, thereby inhibiting the expansion of BOFS aggregates as shown in Equations ( 5) and ( 6) [44,81].…”
Section: Discussionmentioning
confidence: 99%
“…15, x FOR PEER REVIEW 18 of 23 high amounts of f-CaO and f-MgO limits the utilization of BOFS as an aggregate source in OPC concrete: f-CaO and f-MgO react with water at a low hydration rate and induce Ca(OH)2 and Mg(OH)2, leading to significant volume expansion[79][80][81].…”
mentioning
confidence: 99%